Shalawat Badar sebagai Ekspresi Cinta dan Koneksi - Azkia Rahma; Tenny Sudjatnika (Indo Publishing, 2025)
Shalawat Badar is a form of praise that not only reflects Muslims' love for the Prophet Muhammad (peace be upon him) but also serves as a powerful means of spiritual connection. Created by KH. Ali Manshur during the ideological tensions between Nahdlatul Ulama (NU) and the Indonesian Communist Party (PKI) in the 1960s, Shalawat Badar serves as a cultural resistance filled with religious and nationalist significance. With lyrics glorifying the Prophet Muhammad and distinctive local cultural chants, this shalawat has become an integral part of various religious rituals of Indonesian Muslims. Beyond its historical and spiritual significance, Shalawat Badar also has positive psychological effects, such as calming the heart and strengthening social solidarity. Chanted at various sacred moments such as the Prophet's birthday and tahlilan (religious gatherings), this shalawat demonstrates how Indonesian Islam grew peacefully through cultural channels. Shalawat Badar is not merely religious art, but a living legacy that educates the younger generation to love the Prophet in a gentle, contextual, and down-to-earth way.